La Noética Como Recurso Contra La Violencia En Habitantes De Ciudad Juárez - Alvarado, Priscila Montañez; Saucedo, Irene Concepción Carrillo; Del Villar, Oscar Armando Esparza; Vega, Marisela Gutiérrez; Avendaño, Ariagor Manuel Almanza (European Scientific Journal, ESJ, 2017)
Mexico has experienced a resurgence of violence in recent years. First with the femicides, then with the declaration of the Mexican State to drug trafficking. This situation caused the inhabitants of Ciudad Juárez to live under an atmosphere of constant fear, forcing them to change their life dynamics in all its forms. Living under these circumstances has been associated with physical and mental illnesses, such as anxiety, obsessive compulsive disorder, paranoid ideas, fear and hostility among others. However, it has been possible to face this adversity with the motivation to find the meaning of life through spirituality that is fundamental point within the noetic. The purpose of this study was to understand the relationship between noetic and psychological stress symptoms (anxiety, obsessioncompulsion, fear-hostility, paranoid ideation, among others) produced by exposure to violence. The Noetic Goal Search Test (SONG) was used to measure the motivation to find the meaning of life and the Symptom Checklist-90-Revised (SCL-90-R) that measures psychological problems for 287 inhabitants of Ciudad Juárez. Statistically significant correlations were found, from small to moderate, between SCL-90-R subscales and noetic goals, which indicates that having motivation to find meaning of life decreases anxiety levels and symptoms of obsessive compulsion among others . It is concluded that when finding motivation for the meaning of life, there are ways to face the adversity produced by the violence.